Textbooks Evaluation: To what Extent Do the English Textbooks Provide Learning to Promote Cognitive Skill? - Nursyahrifa Nursyahrifa; Mukhaiyar Mukhaiyar; Jufrizal Jufrizal (Metathesis: Journal of English Language, Literature, and Teaching, 2019)
This research mainly aims at conducting an extensive evaluation of the two English textbooks for senior high school grade tenth revised edition based on Kurikulum 2013 yang disempurnakan (curriculum 2013 revised edition). This study employed a descriptive qualitative study. The English textbooks for the tenth grade published by Erlangga and Ministry of Education and Culture were selected as the sources of data. The evaluation focuses on how far the textbooks provide learning to promote cognitive skill. Basic competencies in cognitive domain of curriculum 2013 were adapted as an instrument to evaluate the textbooks. Findings found that the textbooks’ authors of the two textbooks have tried to present opportunities for students to achieve core competencies in cognitive domain of curriculum 2013 in several units. Nevertheless, there are certain units that need additional instructions to provide more opportunities for students in acquiring low and high-order thinking skills. On the basis of the findings, the textbooks may revise or improve the textbooks’ content by adding more experiences for students to achieve the levels of taxonomy bloom expected in the core and basic competencies of curriculum 2013. The findings are also useful for teachers to add or modify the instructions that suit the purposes of curriculum 2013 specifically in cognitive domain.